Rhizodegradation of petroleum oily sludge-contaminated soil by hetero-rhizospheric bacteria from Cajanus cajan (L.) Millsp. (pigeon pea) - Alkali, Allamin Ibrahim (2018)
A significant amount of oily sludge is generated from the petroleum industry during exploration, production, transportation, storage, and refining processes. However, due to the recalcitrant persistent nature of oily sludge, the search for effective treatment method is being intensively sought. Bioremediation has been touted as the most costeffective method in remediating oily sludge pollution with phytoremediation being singled out as the best method. Of all plant types, legume plants are being explored as efficient remediation agents based on their ability to fix nitrogen and harboring numerous xenobiotic-degrading microorganisms in their rhizome. Cajanus cajan a legume plant, has been previously demonstrated on its ability to remediate soil spiked with spent engine oil and even light petroleum crude oil. In this study, the plant was experimented on its ability to remediate the petroleum oily sludge in soil. The plant’s tolerance to the contaminant was monitored through the determination of parameters such as plant height, number of leaves and dry biomass. Culture-dependent and independent methods were used to determine the rhizosphere microorganisms. For culture dependent soil was sampled to determine (total heterotrophic bacteria (THB) using nutrient agar, nitrogen-fixing bacteria (NFB) using yeast extract mannitol agar, and hydrocarbon utilizing bacteria (HUB) using oil agar. Similarly, metagenomics 16s RNA sequencing was used to determine the bacterial community. Degradation rates were estimated gravimetrically and quantified on GC-FID. Accumulation of heavy metals by C. cajan was determined using AAS. The results for the effect of oily sludge to seed germination show a decrease in germination at higher concentrations of oily sludge, especially at 5% oily sludge, which could be due to the reported toxicity of oily sludge to plant germination. The next sets of experiments studied the effect of oily sludge to plant growth parameters compared to control plant with no oily sludge. The plant height at the lower concentrations CR1%, CR2% and CR3% were 28, 26.2 and 25.6 cm, respectively, while at the comparatively higher concentrations at CR4% and CR5%, the heights were 21.1 and 14.1 cm, respectively, while 25.6 cm was the UR (Uncontaminated control) at 28 days of plant growth. The shoot shows a similar pattern to that of the height as at lower concentrations of CR1%, CR2% and CR3% shows 11.3, 11.3, and 11 number of shoots, whereas at the higher concentrations CR4% and CR5%, the number of shoots were 6.3 and 5 after 28 days. The plant growth parameters plant height and number of shoots were not significantly affected by oily sludge at the concentrations of CR1, CR2 and CR3% petroleum oily sludge (w/w) while higher concentrations of CR4 and CR5% significantly reduce these plant growth parameters. The plant growth parameters wet and dry weights of the shoot and root of plant were found to be increased compared to control up to CR3% of oily sludge while higher concentrations were inhibitory as measured based on the wet weights after 60 and 90 days of growth. The relative growth rate (RGR) of the plant at the various treatments from 30 to 90 d shows a significant decrease in rates of growth at the higher concentrations (CR4 and CR5%) compared to control and at lower oily sludge concentrations (CR1, CR2 and CR3%). The RGR of lower concentrations (CR1, CR2 and CR3%) at 60 to 90 d show higher growth rates compared to control. In another sets of experiment, the microbial counts of various soil populations such as total heterotrophic rhizospheric bacterial (THRB), hydrocarbon-utilizing rhizospheric bacterial (HURB), nitrogen-fixing rhizospheric bacterial (NFRB), nitrogen-fixing endophytic bacterial (NFEB), hydrocarbon utilizing endophytic bacterial (HUEB) were determined for various soil treatments. Counts 1% oily sludge shows that the contaminated rhizosphere (CR) microorganism counts increased slightly but significantly (p < 0.05) from 125 x 107 to 148 x 107 CFU/g from 0 days to 90 days. The contaminated non-rhizosphere CN counts were 112 x 107 to 77.3 x 107 CFU/g whereas THRB for the 4 and 5% oily sludge concentrations in the treatments from 0 day to 90 days from 96.7 x 107 to 112 x 107 CFU/g and 57.7 x 107 to 45.4 x 107 CFU/g. The results indicate that the total heterotrophic rhizospheric bacterial (THRB) is significantly higher in contaminated rhizosphere compared to uncontaminated rhizosphere from day 0 to day 90 with a decrease in total count was observed at 4% oily sludge, which is the limit concentration of which the THRB can survive. For the hydrocarbon-utilizing rhizospheric bacterial (HURB), the result shows that for 1% oily sludge concentration, the increased microbial counts in all treatments were observed with the contaminated rhizosphere CR in microbial counts from 31.3 x 107 to 131 x 107 CFU/g, followed by uncontaminated rhizosphere UR from 30 x 107 to 86 x 107 CFU/g, uncontaminated non-rhizosphere UN from 25 x 107 to 58 x 107 CFU/g and the least was contaminated non-rhizosphere CN from 28 x 107 to 54 x 107 CFU/g, the results show that for 1 to 3% oily sludge concentration, the increased microbial counts for all treatments from day 0 to 90 d were observed with the contaminated rhizosphere CR showing the highest significant increase (p < 0.05) in microbial counts compared to other treatments. For the nitrogen-fixing endophytic bacterial (NFEB), the counts measured from 0 to 90 days show higher bacterial counts in the rhizosphere treatments than the non-rhizosphere. At the highest concentration of oily sludge tested (5%), a dramatic drop of NFRB count in the contaminated rhizosphere (CR) plot compared to the unaffected uncontaminated rhizosphere plot suggests that the NFRBs are sensitive to the presence of oily sludge. For the nitrogenfixing endophytic bacterial (NFEB), the result indicates that the nitrogen-fixing endophytic bacteria were also affected by the high concentration of oily sludge but at the lower concentrations, appreciable number of endophytic nitrogen-fixing bacteria was observed. For the hydrocarbon-utilizing endophytic bacterial (HUEB), the HUEB counts were found to exhibit a similar pattern of higher bacterial counts in the presence of oily sludge (CR1 to CR3%) compared to control at all days from 30 to 90 d) and inhibition of counts at higher concentrations of oily sludge at 4 and 5%. A total of 30 hydrocarbon-utilizing rhizosphere and endophytic bacteria were isolated and characterized from the rhizosphere of C. cajan. Through morphological and biochemical identifications, 24 rhizospheric bacteria of which eight were nitrogenfixing rhizospheric bacteria were identified whereas six endophytic bacteria were also identified. Of the 24 rhizospheric bacteria, 11 were Gram-positive bacteria whereas 13 were Gram-negative with Bacillus dominating the Gram-positive species. The calculated bacterial community abundance index showed a slight difference in the Ace, Cho, and Shannon indices. Nevertheless, the Simpson and coverage indices showed a significant difference between the two treatments. The principal component analysis (PCA) plot revealed community level differences between the contaminated non-rhizosphere control (CN3) and contaminated rhizosphere (CR3) microbiota. The component differentiated the two treatments based on the presence or absence of plant. The composition and taxonomic analysis of microbiota amplified sequences were categorized into eight phyla in the contaminated non-rhizosphere (CN3) and ten phyla in the contaminated rhizosphere (CR3). The overall bacterial composition of the two treatments varied, as the distribution show a similar variation between the two treatments in the phylum distribution. The removal rate of total petroleum hydrocarbon (TPH) from the soil after 90 days of treatments was inhibited at higher concentrations of oily sludge composition in the soil with CR1%, CR2% and CR3% (w/w) of oily sludge showed 92%, 90% and 89% removal rate, respectively, and 68.3% and 47.3% removal rate for the relatively higher concentrations of oily sludge of CR4% and CR5% (w/w) respectively. These results were further confirmed by the chromatographic peaks in the GC-FID profile of the treatments. The results of heavy metal shows Pb was accumulated in the CR1 to CR5% oily sludge root of C. cajan was 0.04 mg/kg to 0.18 mg/kg. Likewise Zn was accumulated in the root for the CR1% to CR5% was 2.13 mg/kg to 4.16 mg/kg. The accumulation of Ni was also similar with 1.3 mg/kg was accumulated in the root of C. cajan at CR1% oily sludge which increased to 2.06 mg/kg in CR5% oily sludge. Mn was accumulated in the root of C. cajan with CR1% oily sludge showing a value of 0.4 mg/kg that slightly increases to 0.5 mg/kg in CR5% oily sludge. Cu shows the highest accumulation at higher oily sludge concentrations while Zn was accumulated at higher concentration at the lower oily sludge treatment. Cu was accumulated in the treatment with CR1% oily sludge to a value of 1.9 mg/kg which increased to 6.8 mg/kg in CR5% oily sludge. Cr was slightly accumulated in the root with CR1% oily sludge showing a value of 0.03 mg/kg which slightly increased in CR5% to 0.09 mg/kg. The heavy metal analysis in C. cajan tissues indicated a considerable accumulation of the metals (Pb, Zn, Ni, Mn, Cu and Cr) in the root and stem of the plant, with negligible metal concentrations detected in the plant leaves suggesting a low translocation factor but indicating that C. cajan is resistant to heavy metals. As the search for more eco-friendly and sustainable remediating green plant continues, C. cajan shows a great potential in reclaiming petroleum oily sludge-contaminated soil due to the above properties including resistance to toxic heavy metals from oily sludge. These findings will provide solutions to polluted soils and their subsequent re-vegetation.